2012
DOI: 10.1016/j.pmrj.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Weight‐bearing Status During Rehabilitation After Arthroplasty for Hip Fractures

Abstract: WBAT is associated with a greater likelihood of home discharge and had similar functional outcomes compared with restricted weight bearing. These findings add support for allowing WBAT after arthroplasty for hip fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Similar findings were reported by Wu et al 4 and Siebens et al 5 However, a study with a different focus (all patients allowed immediate WB) showed that surgery on a preholiday was associated with retarded WB (ability to stand for 2 mins within 48 hrs). Similar findings were reported by Wu et al 4 and Siebens et al 5 However, a study with a different focus (all patients allowed immediate WB) showed that surgery on a preholiday was associated with retarded WB (ability to stand for 2 mins within 48 hrs).…”
Section: Baseline Characteristicssupporting
confidence: 85%
See 3 more Smart Citations
“…Similar findings were reported by Wu et al 4 and Siebens et al 5 However, a study with a different focus (all patients allowed immediate WB) showed that surgery on a preholiday was associated with retarded WB (ability to stand for 2 mins within 48 hrs). Similar findings were reported by Wu et al 4 and Siebens et al 5 However, a study with a different focus (all patients allowed immediate WB) showed that surgery on a preholiday was associated with retarded WB (ability to stand for 2 mins within 48 hrs).…”
Section: Baseline Characteristicssupporting
confidence: 85%
“…5,6 However, the decision to allow early, full WB (practiced as WBAT) after hip fracture differs from one country to the next. 1Y4 It has been shown that patients voluntarily limit loading of the fractured limb within the first 3Y4 mos after hip fracture surgery, beyond BWB as tolerated[ (WBAT).…”
Section: Disclosuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of early WB and mobilization on the postoperative functional outcome after a hip fracture has been evaluated in a number of studies. [35][36][37] Yet, there is a lack of knowledge about the influence of the WB status specifically on mortality after hip fracture. Several studies 4,20 have explored complications such as respiratory disease as a risk factor of mortality, but it is not known whether these complications could be due to late WB and mobilization.…”
Section: Wb Statusmentioning
confidence: 99%